Controlling the Morphology of PVDF Hollow Fiber Membranes by Promotion of Liquid–Liquid Phase Separation. Issue 7 (14th April 2018) - Ghodsi, Ali; Fashandi, Hossein; Zarrebini, Mohammad; Mirzaei, Majid
Abstract : In literature, liquid–liquid (L–L) phase separation has been widely adopted as the principle technique by which polymeric membranes are produced. However, the promotion of L–L phase separation as the means of controlling membrane morphology is still debatable. Thus, this work aims to introduce a facile and cost‐effective technique for controlling the morphology of poly(vinylidene fluoride) (PVDF) hollow fiber membranes (HFMs). The proposed technique is based on promotion of L–L phase separation which can be achieved through two different approaches: 1) reducing the distance between locations of dope and binodal curve through locating spinning dope on nonsolvent (water)/solvent (2‐pyrrolidone)/polymer (PVDF) ternary phase diagram by increasing of nonsolvent content and maintaining of polymer concentration at initial level; 2) simultaneous occurrence of thermally and nonsolvent induced phase separation (TNIPS). It is found that L–L phase separation promotion based on the above described approaches yields to PVDF HFM with partially double‐layered structure, enhanced mechanical properties, higher porosity, and smaller average pore radius with the potential to purify textile wastewater containing C.I. Disperse Violet 33. The proposed technique is advantageous due to lack of need for additives or post‐treatment process for HFM synthesis. Abstract : A facile and cost‐effective technique for controlling the morphology of PVDF hollow fiber membranes (HFMs) is provided based on promotion of L–L phase separation through (I) Reducing the distance between locations of dope and binodal curve, (II) Simultaneous occurrence of thermally and nonsolvent induced phase separation (TNIPS). PVDF HFMs with the potential to purify disperse dye wastewater are developed.